Prevalence of lung cancer in Isfahan Province, Iran - Zahra Tolou_Ghamari (Journal of the Egyptian National Cancer Institute, 2018)
Objective: To describe for the first time period prevalence (PP) and incidence rate (Ir) for patients with lung cancer in Isfahan Province/Iran. Design: Data associated to the Surveillance, Epidemiology, and End Results; (SEER) was collected from the Isfahan Cancer Registry from March 2011 to March 2015. Lung cancer was distinguished by the related established topography code. PP and Ir were calculated and expressed per 100,000 persons. Results: In all, 548 females and 1399 males were identified. For the total population the PP was calculated as 39.1 (distinguished as: 30.7 for bronchus and lung, 7.9 for larynx and 0.5 for trachea). This value corresponded to a PP of 55.3 for males and 22.3 for females (p < 0.001). Irs versus mortality rates were calculated for each year, i.e. 2011–2012, 2012–2013, 2013–2014, and 2014–2015, as 9.3 vs 6.3, 10.1 vs 6.6, 9.9 vs 6.3, 9.6 vs 6.4, respectively. The mean (SD, range) age of the patients was 65.8 (14.7, 1–103) years. In relation to the age of study population, lung cancer occurred in 94% of patients aged between 40 and 90 years. Conclusion: The PP for lung cancer in male population was 2.5 times higher than females. There was a 3.2% increase in the Irs over the study period. To facilitate early diagnosis for better management associated to pharmacotherapy or surgical care, our findings emphasized the advantage of further research and greater effort toward environmental, job related exposure, genetic and geographical factors in Isfahan Province/Iran. Keywords: Cancer, Prevalence, Iran, Lung, Respiratory